The Effectiveness of Song Hye-kyo as a Brand Ambassador for Collagena among the Indonesian Public - Evania Christiyanto; Lady Joanne Tjahyana; Felicia Goenawan (Journal of Content and Engagement, 2025)
Collagena is the first collagen milk brand in Indonesia, produced by PT Mayora Indah Tbk. To support its marketing public relations strategy, the company appointed South Korean actress Song Hye-kyo as its brand ambassador, leveraging her youthful image and strong public appeal. This study aims to examine the effectiveness of Song Hye-kyo as the brand ambassador for Collagena in Indonesia. A quantitative method was employed through a survey distributed to 400 respondents using Google Forms. The data were measured using a Likert scale and analyzed descriptively. The study adopts the VisCAP theory, which includes visibility, credibility, attraction, and power, to assess ambassador effectiveness. The findings reveal high effectiveness across all indicators, with power emerging as the strongest dimension and credibility as the least, though still favorable. Generational analysis indicates that Generation Z responds most to power, Millennials to attraction, and Generation X to visibility. These results highlight the alignment between Song Hye-kyo’s persona and Collagena’s brand image, demonstrating her significant role in enhancing marketing public relations efforts. The study offers valuable insights for practitioners seeking to optimize brand ambassador selection in marketing communication strategies.